Improving Students' Speaking Skills in English Language Learning Through Storytelling - Yus Vernandes Uzer; Yuspar Uzer (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine how students' speaking skills improve in English learning through storytelling. By understanding how this improvement occurs, prospective educators are expected to be able to apply several interesting teaching methods to improve students' English speaking skills. This study is a classroom action research and consists of two cycles. The methodology used is quantitative research. The results of this study indicate that students' speaking skills improve after being taught through storytelling. The students are more imaginative in demonstrating their understanding of the story. It makes them motivated to learn and they can improve their speaking skills. The average score of students before the implementation of storytelling is 48 and the average score of students after implementing storytelling is 84. Thus, Improving Students' Speaking Skills in English Learning Through Storytelling is very effective to implement as long as it is fun and easy to understand by students at SMA Patra Mandiri 01 Palembang.